A proteome-wide association study reveals novel plasma proteins as potential therapeutic targets for metabolic dysfunction-associated steatotic liver disease - Zhong, Qian; Zhu, Yue; Tan, Yiwen; Deng, Wenzeng; Wang, Chunxia; Yang, Shan; Tong, Nanwei (Frontiers in Endocrinology, 2025)
IntroductionMetabolic dysfunction-associated steatotic liver disease (MASLD) is a growing global health burden with limited therapeutic options. To identify novel proteins involved in its pathogenesis and reveal potential drug targets, we performed an integrative analysis combining plasma proteomic data with genome-wide association study (GWAS) summary statistics for MASLD.MethodsA proteome-wide association study (PWAS) was conducted by integrating plasma protein quantitative trait loci (pQTL) data with GWAS summary statistics from the FinnGen R11 MASLD cohort (used as the discovery dataset) and a large-scale MASLD GWAS meta-analysis (used for validation). Causal inference was assessed using Mendelian Randomization (MR), and Bayesian colocalization was applied to identify shared genetic signals. Additionally, liver specimens from five healthy controls and five MASLD patients were subjected to H&E and NCAN immunohistochemistry.ResultsPWAS in the discovery cohort identified three plasma proteins—NCAN, EPHA2, and APOE—significantly associated with MASLD risk. Among them, NCAN showed the strongest and most consistent association, which was replicated in the validation cohort. MR analyses supported a causal role for NCAN in both cohorts, whereas colocalization at the NCAN locus was suggestive rather than definitive. Immunohistochemical analysis showed that NCAN expression was significantly reduced in MASLD liver tissues.ConclusionsThis integrative proteomic and genetic study identified NCAN as a key contributor to MASLD pathogenesis. Its consistent association and genetic evidence across two independent cohorts highlight NCAN as a promising therapeutic target that merits further functional investigation.